2020
DOI: 10.1029/2020jg005748
|View full text |Cite
|
Sign up to set email alerts
|

Maximum Carboxylation Rate Estimation With Chlorophyll Content as a Proxy of Rubisco Content

Abstract: The maximum carboxylation rate (Vcmax) is a key parameter in determining the plant photosynthesis rate per unit leaf area. However, most terrestrial biosphere models currently treat Vcmax as constants changing only with plant functional types, leading to large uncertainties in modeled carbon fluxes. Vcmax is tightly linked with Ribulose‐1,5‐bisphosphate carboxylase/oxygenase (Rubisco). Here we investigated the relationship between leaf chlorophyll and Rubisco (Chl‐Rub) contents within a winter wheat paddock. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 79 publications
(144 reference statements)
2
26
0
Order By: Relevance
“…This is because enzymatic reactions are faster at high temperatures; therefore, warm‐grown plants can achieve optimal net CO 2 assimilation rates with a relatively lower photosynthetic enzyme content (Smith & Keenan, 2020; Yamori et al, 2014). Since both Rubisco carboxylation and electron transport rates, and the contents of the enzymes that regulate each process (Rubisco and chlorophyll pigments) are co‐regulated (Lu et al, 2020; Maire et al, 2012; Wullschleger, 1993), then warm acclimated plants should consequently reduce both V cmax and J max . Since respiration is involved in providing energy for protein turn over, which is the largest factor that explains variation in leaf R d , then thermal acclimation of respiration should closely follow that of photosynthetic capacity (Wang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…This is because enzymatic reactions are faster at high temperatures; therefore, warm‐grown plants can achieve optimal net CO 2 assimilation rates with a relatively lower photosynthetic enzyme content (Smith & Keenan, 2020; Yamori et al, 2014). Since both Rubisco carboxylation and electron transport rates, and the contents of the enzymes that regulate each process (Rubisco and chlorophyll pigments) are co‐regulated (Lu et al, 2020; Maire et al, 2012; Wullschleger, 1993), then warm acclimated plants should consequently reduce both V cmax and J max . Since respiration is involved in providing energy for protein turn over, which is the largest factor that explains variation in leaf R d , then thermal acclimation of respiration should closely follow that of photosynthetic capacity (Wang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Our study showed that V cmax andJ max calculated by RACiR curves under multiple [CO 2 ] gradients were not significantly different from TACiR curves, indicating that the RACiR technique could be applied to herbs as well as evergreen species (Pilon et al 2018, Lu et al 2020, McKenzie-Gopsill et al 2020, Vincent et al 2020, Liu and van Iersel 2021 and thus is likely to be generalizable among different plant life forms.…”
Section: Racir Technique Could Be Applied To Evergreens and Herbsmentioning
confidence: 71%
“…As opposed to most previous studies conducted at the local scale (Croft et al, 2015(Croft et al, , 2017Lu et al, 2020), this study presented a large-scale pattern of leaf Chl among 677 site-species across grasslands on the Tibetan Plateau. Surprisingly, we found that plant evolutionary history was more dominant than current environmental changes in impacting the regional patterns of leaf Chl.…”
Section: Discussionmentioning
confidence: 87%